b/a+a/b=3,求2ab/(a*a+b*b)-(3a*a+ab+3b*b)/2ab的值
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 20:36:10
b/a+a/b=3,求2ab/(a*a+b*b)-(3a*a+ab+3b*b)/2ab的值b/a+a/b=3,求2ab/(a*a+b*b)-(3a*a+ab+3b*b)/2ab的值b/a+a/b=3,
b/a+a/b=3,求2ab/(a*a+b*b)-(3a*a+ab+3b*b)/2ab的值
b/a+a/b=3,求2ab/(a*a+b*b)-(3a*a+ab+3b*b)/2ab的值
b/a+a/b=3,求2ab/(a*a+b*b)-(3a*a+ab+3b*b)/2ab的值
因为b/a+a/b=3
所以a²+b²=3ab
那么 2ab/(a*a+b*b)-(3a*a+ab+3b*b)/2ab
=2ab/3ab-(9ab+ab)/2ab
=-13/3
已知3a*a+ab-2b*b=0(a不等于0,b不等于0),求a/b-b/a-(a*a+b*b)/ab的值.
a(a-1)-(a×a-b)=-5,求(a×a+b×b)÷2-ab
b/a+a/b=3,求2ab/(a*a+b*b)-(3a*a+ab+3b*b)/2ab的值
已知a*a-ab=3,ab+b*b=-5,求代数式a*a+b*b与a*a-2ab-b*b的值
ab=-2 a+b=3 求ab(a²+b²)-a-b
(a-b)(a^2+b^2+ab)/3-a^2b+ab^2=(a-b)^2,且a不等于b求a-b的值
若a/b+b/a=3,求a^2+ab+b^2/a^2-ab+b^2的值
已知a,b满足a+b=5,a-b=1,求ab,a^2+b^2-3ab
(a-2b)(a^2+2ab+4b^2)-a(a+3b)(a-3b),其中a=-1/9,b=1求a,b
若a/b=2,求分式a*a+ab-b*b/a*a-2ab+2b*b
已知a+2b=0,求a*a+2ab-b*b/2a*a+ab+b*b
已知a(a-1)-(a^-b)=3,求a^2+b^2-2ab
已知(a+b)(a+b)=20,ab+2,求(a-b)(a-b)的值
a^3-ab^2 =a (a^2 -b^2) =a(a+b)(a-b)
若ab不等于0,且3a=b,求代数式b/3a-(-b)/a-a/2b/(-b)
已知a+b=A,ab=A+2008,1-2(a+ab)+(ab-2b)=3A.求a+b和ab的值
已知a+b=A ab=A+2008 1-2(a+ab)+(ab-2b)=3A 求a+b ab的值
已知a+b=A ab=A+2008 1-2(a+ab)+(ab-2b)=3A 求a+b ab的值